Time-synchronic comments on video streaming website reveal core structures of audience engagement in movie viewing - Ni, Wenjing; Coupé, Christophe (Frontiers in Psychology, 2023)
To what extent movie viewers are swept into a fictional world has long been pondered by psychologists and filmmakers. With the development of time-synchronic comments on online viewing platforms, we can now analyze viewers’ immediate responses towards movies. We collected over 3 million Chinese time-synchronic comments and applied natural language processing (NLP) techniques to investigate linguistic patterns under different movie genres. We first highlight different commenting behaviors in front of various movies and how comments are organized in a range of topics. Through the assessment of emotion and cognition-related word rates in comments, we further identify how topics are discussed through time, as well as prototypical diachronic trajectories of psychological engagement of the audience. We then try to account for viewer’s engagement, considering successively movie genres, topics and movie content. Among other points, we finally discuss the challenge in explaining the trajectories of engagement and the disconnection with narrative content. Overall, our study provides a new perspective on using social media data to answer questions from psychology and film studies. It underscores the potential of time-synchronic comments as a resource for detecting real-time human responses to specific events.